Investigating Sound Design in Film: A Commentary on Kock and Louven - Tan, Siu-Lan (Empirical Musicology Review, 2019)
Kock and Louven (in this issue) examined the effects of music, sound effects, full sound design (music and sound effects) and no sound on self-reported measures of immersion and suspense in real time, as viewers watched very brief original films. This commentary discusses the method, analysis, and implications of their findings within the broader context of the state of the art of film music research, and future directions for investigations in this area.